Incidence and characteristics of severe exercise-associated collapse at the world’s largest half-marathon - Lüning, H.; Mangelus, C.; Carlström, E.; Nilson, F.; Börjesson, M. (PloS one, 2019)
Whilst many health benefits are associated with regular exercise, medical complications may occur during higher-intensity activities, such as long distance running contests. The most common complication is collapse. However, the incidence and characteristics of these collapses are not very well studied. This is a retrospective study of severe collapse, defined as a patient in need of advanced medical care after a collapse, during the large Gothenburg's half marathon, Göteborgsvarvet. The study included 230,501 competitors during the study-period of 5 years (2013-2017) with data being collected from medical race tents and using ambulance data. Vital signs, treatment and blood gas samples were noted and analyzed. The incidence of severe collapse was 1.53 per 1000 starting runners. The average age for patients was 34 years old and no difference in incidence were seen between male and female runners. The typical collapsed runner presented with tachycardia, normal systolic blood pressure, elevated body temperature and metabolic acidosis. The most common medical encounter was exercise-associated collapse. The incidence of severe collapse was similar to findings in other studies, even though this study was set in different part of the world. Typical characteristics of a collapsed runner were identified providing new information which could be beneficial in the medical planning of larger running competitions and future preventative interventions. Importantly, life threatening conditions seem uncommon; no case of hyponatremia and only two cases of hypoglycemia were seen.